STUDY OF DEGRADATION AND GRANULAR FLOW PROCESSES USING X-RAY IMAGING - Babout , Laurent; Grudzień, Krzysztof; Janaszewski, Marcin; Jopek, Łukasz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
This paper reviews the work that has been done in the past 10 years at the Lodz University of technology about the visualization and the quantification of phenomena related to degradation processes (i.e. stress corrosion cracking in stainless steel, fatigue crack in titanium alloys) in engineering materials as well as granular flow in silos using X-ray imaging (i.e. radiography and (micro)tomography). Besides presenting the experimental protocols, the paper also presents the image processing strategies that have been applied to enable the extraction of characteristic parameters from the volumetric images.